Jenis-Jenis Jamur pada Pembusukan Buah Kakao (Theobroma cacao, L.) di Sumatera Barat - Yenita Afriyeni; Nasril Nasir; - Jumjunidang (Jurnal Biologi Universitas Andalas, 2013)
Currently, cacao (Theobroma cacao, L.) farm is being developed in West Sumatra as one of the most potential estate crops. Less than 10 years, the crop had been developed up to 110,000 ha whereas it was only 25,000 ha in 2005. However there is none of the crops free from disease of immature fruit decay. The aim of this study was to identify the fungus which were collected on decay fruits of cocoa. Samples were collected from lowland and highland farms in West Sumatera by purposive sampling method. Fungus found on the decay fruit of cocoa in the lowland were Phytophthora palmivora, Fusarium sp and Aspergillus niger, while in highland were P. palmivora, Fusarium sp and Gloeosporium.Keywords: cacao, fungus identification, decay fruit.